2016
DOI: 10.1039/c6cc00838k
|View full text |Cite
|
Sign up to set email alerts
|

A nanofiber assembly directed by the non-classical antiparallel β-structure from 4S-(OH) proline polypeptide

Abstract: The antiparallel arrangement of two strands of the non-classical β-structure, formed exclusively via cis-4S-(OH) prolyl polypeptide as established by FRET, propagates into self-assembled nanofibers upon conjugation with C12/C14/C16 hydrocarbon chains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 41 publications
4
24
1
Order By: Relevance
“…Here we conjecture that the two chains in β‐structure may have similar dihedral angles as in PPII conformation, and β‐structure may arise from hydrogen bonding between side chain (OH/NH) groups of one chain and the backbone carbonyl oxygen of another chain. We emphasize that the present results do not provide any direct experimental evidences for the microstructural details of proline pucker, amide bond geometry or the exact hydrogen bonding patterns, but the antiparallel orientation of the two chains of β‐structure is evident from our recent work …”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Here we conjecture that the two chains in β‐structure may have similar dihedral angles as in PPII conformation, and β‐structure may arise from hydrogen bonding between side chain (OH/NH) groups of one chain and the backbone carbonyl oxygen of another chain. We emphasize that the present results do not provide any direct experimental evidences for the microstructural details of proline pucker, amide bond geometry or the exact hydrogen bonding patterns, but the antiparallel orientation of the two chains of β‐structure is evident from our recent work …”
Section: Discussioncontrasting
confidence: 62%
“…The proposed β‐structure here (Figure B) is unusual in the sense that it originates from H‐bonding of acceptor carbonyl amide on backbone with the side chain donor amino group on the opposite chain. By employing FRET and FESEM, we have recently shown that the orientation of two strands of β‐structure in (4 S )‐ Hyp 9 is antiparallel . In this orientation, by retaining the C4‐ endo pucker, C4( S )‐NH 2 /OH/NHCHO peptides can in principle form both interchain and intraresidue H‐bonds, (Figure B,D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, isomerization of P II helix can proceed into a nonclassical backbone‐side chain hydrogen‐bonded β‐sheet‐like assemblies (in trifluoroethanol). The latter were documented only very recently for peptides formed by specific proline analogues …”
Section: Introductionmentioning
confidence: 95%
“…4,[13][14][15] However, segments that adopt PPII-like structures have been observed in short polypeptides and proteins. [16][17][18][19] PPII-like segments with a minimum of length two residues and a maximum of 14 residues has been observed to date. 16,20 While Pro-rich regions show a preference for the PPII structure, host-guest based analysis using Pro-containing sequences as the host revealed that when Gln, Asp, Gly, and Ala (guest) are incorporated, the guest residues can adopt the PPII form.…”
mentioning
confidence: 99%